2008
DOI: 10.3201/eid1410.080522
|View full text |Cite
|
Sign up to set email alerts
|

Control Strategy forEchinococcus multilocularis

Abstract: Echinococcus multilocularis , the causative agent of zoonotic alveolar echinococcosis, can be controlled effectively by the experimental delivery of anthelminthic baits for urban foxes. Monthly baiting over a 45-month period was effective for long-lasting control. Trimonthly baiting intervals were far less effective and did not prevent parasite recovery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
37
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(37 citation statements)
references
References 14 publications
0
37
0
Order By: Relevance
“…Inoue et al highlighted the importance of frequent baiting (monthly) at least during periods (summer, autumn) where transmission is considered high (Inoue et al, 2007). König et al (2008) and Hegglin et al (2008) also highlighted the need for frequent baiting (monthly). Romig and colleagues (2007) showed that baiting with six week intervals reduced the prevalence, when increasing the baiting interval to 3 months (after 21 months) the prevalence stabilised and increasing it to 6 months resulted in an increase in prevalence.…”
Section: Tor2b)mentioning
confidence: 99%
See 1 more Smart Citation
“…Inoue et al highlighted the importance of frequent baiting (monthly) at least during periods (summer, autumn) where transmission is considered high (Inoue et al, 2007). König et al (2008) and Hegglin et al (2008) also highlighted the need for frequent baiting (monthly). Romig and colleagues (2007) showed that baiting with six week intervals reduced the prevalence, when increasing the baiting interval to 3 months (after 21 months) the prevalence stabilised and increasing it to 6 months resulted in an increase in prevalence.…”
Section: Tor2b)mentioning
confidence: 99%
“…König et al (2008) showed that the prevalence in foxes could be reduced to close to zero in less than one year by intensive baiting (every four weeks initially and then every sixth week) and combining arial distribution with distribution by hand at strategic places identified in previous studies. However, Hegglin et al (2008) highlighted that, if local disappearance of the parasite is to be obtained, intensive baiting should be continued even after the prevalence has decreased drastically.…”
Section: Tor2b)mentioning
confidence: 99%
“…This has stimulated pilot control programmes to treat foxes and it has been shown that distributing fox baits containing praziquantel on a regular basis can substantially reduce the prevalence of E. multilocularis in foxes (Hegglin and Deplazes, 2008). The question remains as to the cost effectiveness of this intervention as it is still uncertain to what extent the human incidence is likely to decrease from such a programme.…”
Section: Alveolar Echinococcosismentioning
confidence: 99%
“…However, therapeutic use of anthelmintics often requires multiple doses to clear infection (Overgaauw 1997), and it is recommended that raccoons taken into captivity receive multiple treatments to ensure complete elimination of B. procyonis (Kazacos 2001). Management applications of anthelmintic baits for B. procyonis mitigation will require repeated bait distribution because of the potential for raccoons to be reinfected from environmental reservoirs (Hegglin and Deplazes 2008;Page et al 2011;Smyser et al 2013). Therefore, should initial bait contact result in reduction, but not elimination, of B. procyonis infections, raccoons likely would receive additional treatments with subsequent bait distribution.…”
Section: Discussionmentioning
confidence: 99%